a artikel Mediasi Orang Tua dalam Pemanfaatan YouTube Sebagai Stimulasi Bahasa Anak Usia Dini Di Desa Bicorong, Pamekasan - Imelyatun Namilah; Thorik Aziz (Universitas Islam Lamongan, 2026)
This study was motivated by the phenomenon that control over YouTube use among early childhood had tended to focus primarily on screen time duration, while in-depth and specific investigations into the role of parental mediation in utilizing YouTube as a medium for language development stimulation—particularly within rural contexts—remained limited. This study aimed to analyze the forms of parental involvement in mediation, the types of educational YouTube content selected, and their impact on early childhood language development in Bicorong Village, Pamekasan. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation. The participants consisted of six parents and six children aged 3-6 years, selected through purposive sampling based on regular parental assistance during children’s access to educational YouTube content. The findings reveal three primary forms of parental involvement: Restrictive mediation, co-viewing, and active mediation. The most frequently accessed content included children’s songs, illustrated storytelling, letter recognition, and basic vocabulary videos, with an average viewing duration of 15-30 minutes per session, 3-5 times per week. Observed outcomes in children’s language development included increased expressive vocabulary, improved pronunciation clarity, greater speaking confidence, and early literacy awareness such as letter recognition. This study addresses a gap in previous research that largely emphasizes screen time duration without examining active parental mediation. Drawing on Vygotsky’s sociocultural theory, parental involvement functions as scaffolding within the Zone of Proximal Development (ZPD), supporting effective language stimulation through digital media.